Detection by action: neuropsychological evidence for action-defined templates in search. - Humphreys, G; Riddoch, M (2001)
How do we detect a target in a cluttered environment? Here we present neuropsychological evidence that detection can be based on the action afforded by a target. A patient showing symptoms of unilateral neglect following damage to the right fronto-temporal-parietal region was slow and sometimes unable to find targets when they were defined by their name or even by a salient visual property (such as their color). In contrast, he was relatively efficient at finding a target defined by the action it afforded. Two other patients with neglect showed an opposite pattern; they were better at finding a target defined by its name. The data suggest that affordances can be effective even when a brain lesion limits the use of other properties in search tasks. The findings give evidence for a direct pragmatic route from vision to action in the brain.